Variable water quality of domestic wells emphasizes the need for groundwater quality monitoring and protection: Stinkwater, Hammanskraal, Gauteng - Baloyi, Rhulane S; Diamond, Roger E (Water SA, 2019)
Groundwater is a critical water resource in many peri-urban areas without municipal water supply, a common situation globally, but especially in Africa. These areas contain multiple water pollution risks from various human activities, including small industry, dumping, stock and pet animals, and pit latrines. Stinkwater village, 40 km north of Pretoria in Gauteng Province, that has only partial municipal water supply, was sampled for water quality from municipal taps, boreholes and open hand-dug wells. The water quality varied greatly, with few obvious geographic or geochemical correlations, other than high bacterial counts in the open wells. The key health concerns were nitrate, fluoride and coliform bacteria (including E. coli), some at dangerous levels. Relatively subtle variations in land use, including water use and pollution sources, as well as vadose zone character, including depth to water table, permeability and recharge pathways, could account for much of the variation in water quality. The study reveals the risk of relying upon a single water quality analysis to determine groundwater conditions for an area. In areas with multiple possible pollution sources, thorough groundwater monitoring is needed to determine the usability of water resources.